Prevention and treatment of anthracycline-induced cardiotoxicity: a systematic review and network meta-analysis of randomized controlled trials - Siyu Li; Wenrui Li; Mengfei Cheng; Xiaoxiao Wang; Wanyi Chen (Cardio-Oncology)
Abstract Background Anthracyclines are cornerstone chemotherapeutics, but cardiotoxicity limits their use. Objective This study aims to evaluate the efficacy of various drugs in preventing and treating anthracycline-induced cardiotoxicity (AIC). Methods We conducted an extensive search across seven databases to identify randomized controlled trials (RCTs) pertinent to the prevention and treatment of AIC with medications. Subsequently, a Bayesian Model-based network meta-analysis was performed in the R 4.4.0. Results A total of 128 RCTs involving 10,431 cancer patients treated with anthracyclines and 78 drug regimens were included in this study. The network meta-analysis results showed that, compared with patients who did not receive cardioprotective drugs, those treated with Calcium Dibutyryladenosine Cyclophosphate (Mean Difference [95% Credible Interval], 8.760 [0.5917, 16.92]), Carvedilol (4.024 [0.5372, 7.656]), Carvedilol + Candesartan (7.934 [3.159, 12.91]), Compound Salvia Miltiorrhiza + Levocarnitine (9.087 [0.9160, 17.25]), Dexrazoxane (5.066 [2.589, 7.540]), Dexrazoxane + Cinobufacini (11.61 [4.590, 18.70]), Dexrazoxane + Shenqi Fuzheng (13.05 [4.640, 21.40]), Nicorandil (14.24 [5.122, 23.31]), Qiliqiangxin (11.38 [2.826, 19.91]), and Xinmai Long (6.371 [1.735, 11.02]) experienced less decrease in LVEF after chemotherapy. The SUCRA ranking results indicated that the most effective treatment option for preserving LVEF was Nicorandil (SUCRA 91.76%). Conclusion Apart from Dexrazoxane, Carvedilol, a β-blocker, also appears to show significant potential in preventing AIC. Furthermore, our results indicate that there is insufficient evidence to support the beneficial effects of statins, Sildenafil, Ivabradine, Levocarnitine, N-acetylcysteine, Glutathione, Coenzyme Q10, Vitamin E, and Vitamin C in preventing LVEF decline and exerting a positive effect on the prevention of AIC.